Perspektif Siswa tentang Proses Pengajaran dan Pembelajaran Bahasa Inggris di MI Azzainiyah II - Islam, Syaiful; Al Faqih, Muhammad Imamuddin; Syahraen, Agie (Universitas Nurul Jadid, 2021)
Learning English does not only apply to junior high school or high school but can be started from elementary school. Early childhood students must learn English early to prepare them for the era of globalization. There are four problem formulations studied, namely about 1) the qualifications of English teachers, 2) students' attitudes towards English, 3) the techniques used, and 4) the media. This study used a qualitative descriptive design. The research subjects consisted of a teacher and 26 fifth-grade students (V) of MI Azzainiyah II Paiton Probolinggo. There are three data collection instruments, namely observation, interviews, and questionnaires. Observations are made when teaching and learning activities are in progress. After that, interviews with teachers were conducted to obtain information related to problem formulations. The questionnaire was given to students to find out students' attitudes towards English. The results showed that 1) the qualifications of the English teachers had good qualifications, 2) the students' attitudes towards English were very positive, 3) the techniques used were varied, including Listen-Do, Listen-Repeat, and Question and Answer, and 4) media that used in the form of pictures from various sources as well as blackboards.